Identification of Sea Level Rise and Land Subsidence Based on Sentinel 1 Data in the Coastal City of Pekalongan, Central Java, Indonesia - Lessy Andari; Denny Nugroho Sugianto; Anindya Wirasatriya; Satria Ginanjar (Jurnal Kelautan Tropis, 2023)
Sea level rise is a pure impact of climate change. However, the process of studying sea level rise must include local factors that influence such as land subsidence. This study focuses on sea level rise using the CEEMDAN method and land subsidence using the DInSAR method. The location of this research is Pekalongan, Central Java, Indonesia. Tidal data used in this study was for five years, from 2016 to 2020, obtained from the Geospatial Information Agency (BIG). Then the data used to study land subsidence in this study uses Sentinel-1 Synthetic Aperture Radar (SAR) data in 2015, 2016, 2017, and 2020. Pekalongan is an area with mixed diurnal tidal types with Formzahl number 1.7. The sea level rise in Pekalongan is relatively high, at 10.6 mm/year. Then the land subsidence that occurred in Pekalongan is the phenomenon that has the most influence on the occurrence of coastal flooding in the region. The average land subsidence on the coast of Pekalongan is 5.37 cm/year. In addition, the sampling results in 6 areas showed that the most significant decrease was in Area 2, with a decrease of -7.91 cm/year. Based on this research, land subsidence is the most considerable influence on flooding in Pekalongan compared to sea level rise.